Unemployment (Relations industrielles / Industrial Relations, 1959)
SummaryThe present size and persistence of unemployment in Canada, andespecially in Quebec, cannot help worry the observers of our economic life, and more so the workers themselves who are directly concerned. It may therefore be useful to reproduce here the full text of the Briefon Unemployment submitted jointly by the Quebec Federation of Labor (CLC) and the Canadian and Catholic Confederation of Laborto the provincial (Quebec) Cabinet on June 13, 1958.